Pendampingan UMKM melalui Pemanfaatan Digital Marketing pada Platform E-Commerce: UMKM Assistance through the Utilization of Digital Marketing on the e-Commerce Platform - Kamil, Indriyati; Bakri, Asri Ady; Salingkat, Suhartini; Ardenny, Ardenny; Tahirs, Jemi Pabisangan; Alfiana, Alfiana (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
In the era of the industrial revolution 4.0 and the increasingly intense efforts to become society 5.0, researchers held training & workshops on technology utilization in the Multipurpose Building with technology training materials. This research aims to carry out MSME Assistance (Micro, Small, and Medium Enterprises) through Google My Business to use digital marketing in the era of e-commerce & social media. The method used in this PkM is the mentoring method or PAR (Participatory Action Research), with an approach through training, account creation practice, and mentoring. The training is carried out in three stages: preparation, implementation, and evaluation. The result of the dedication to Digital marketing for a company and MSMEs is an essential part currently. MSME managers are expected to have skills in internet promotion through digital devices, especially in publishing products for sale and places offered. It can be concluded that community assistance in managing their business to better manage marketing activities through creating Google My Business application accounts in digital marketing.